Banksy`ego/Banksym walka o obiektyw turysty. Notatki o oporze w przestrzeni miasta = Banksy`s/with Banksy struggle for tourists` lens. Notes on resistance in urban space - Frąckowiak, Maciej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Banksy is a protesting graffiti artist of international fame who has made the dominant images of the city the material for his artistic activity. It is the city that enables his works and in this sense they are symptomatic of him. If so, then through the prism of these works, as if through a lens, one can read the contemporary Western city, both as a certain architectural-market-administrative idea and the processes taking place in it. It is this perspective that I would like to adopt below.
Keywords: Banksy (brytyjski artysta street-art; 1974- ); miasto; street-art